Area postrema syndrome as the only sign of medullary infarction adjacent to area postrema - Patrick Stancu; Nicolae Sanda; Karl-Olof Lovblad; Nils Guinand; Andreas Kleinschmidt; José Bernardo Escribano Paredes (eNeurologicalSci)
Area postrema syndrome (APS) is characterized by acute or subacute intractable nausea, vomiting, and/or hiccups lasting for at least 48 h. These symptoms can occur individually or in combination and are typically linked to periventricular brainstem lesions, particularly involving the area postrema (AP). The AP, a highly vascularized circumventricular organ located in the dorsal medulla oblongata, is supplied by the anterior spinal artery and perforating branches of the posterior inferior cerebellar artery (PICA), making it susceptible to pathological processes that can lead to APS. APS rarely occurs in stroke patients, but has been seen with ischemic lesions in the medial brachium pontis. The underlying pathophysiology of APS remains unclear, but remote lesions from the AP suggest involvement of an autonomic network of neuronal structures. This article reports a rare case of APS caused by ischemic stroke near the area postrema, without accompanying neurological impairments. The case highlights the importance of vascular investigation in intractable APS cases, even without focal neurological symptoms, and supports the role of neuronal structures connected to the AP in APS development.